Generating electric vehicle load profiles from empirical data of three EV fleets in Southwest Germany. (1st May 2017) - Schäuble, Johannes; Kaschub, Thomas; Ensslen, Axel; Jochem, Patrick; Fichtner, Wolf
Abstract: The increasing demand for electricity caused by a growing number of electric vehicles (EV) might challenge future energy systems. For a smooth integration of the electricity demand from EV, a comprehensive knowledge of its characteristics is essential. The analysis of charging behavior patterns of EV and resulting load profiles become important premises for this crucial task. Three electric mobility studies in Germany's southwestern region (Get eReady, iZEUS, and CROME) deliver comprehensive data of EV use for this purpose. In this paper we analyze and discuss the mobility and charging characteristics of this data in detail. We derive empirical EV load profiles and show how they are affected by charging management. We present a model to simulate EV loads based on statistical characteristics of the conducted studies. The resulting charging load profiles show similar patterns as other EV studies. The developed simulation model and its results (see supplementary data available online) allow a realistic representation of EV demand in analyses of future energy systems. Graphical abstract: